Analisis Peran Donor MDGs dalam Pembangunan Ekonomi Indonesia: Tinjauan Ekonomi Politik - Latifa, Asma; Magriasti, Lince (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to analyze the role of Millennium Development Goals (MDGs) donors in Indonesia's economic development through a political economy approach. The background of this research underscores the significance of international donors in fostering economic development in developing countries, including Indonesia. The research question addresses how MDGs donors contribute to Indonesia's economic development and the interaction between such international aid and the political economy dynamics within the country. The research employs qualitative analysis through literature reviews and in-depth interviews with experts and practitioners in economic development and public policy. The findings reveal that MDGs donors have significantly contributed to several development sectors, such as health and education, but there are challenges in the sustainability and effectiveness of this aid due to domestic and global political factors. The study concludes that the role of MDGs donors in Indonesia's economic development is heavily influenced by the political economy context, and more adaptive strategies are required to enhance the effectiveness of international aid in supporting sustainable development.